Henry Derozio, the Eurasian poet and reformer - Madge, Elliot Walter (Naya Prokash, 1982)
Author's lecture at Y.M.C.A. Hall, Calcutta, 1904, on the life and poetry of Henry Louis Vivian Derozio, 1809-1931, professor of Hindu College, Calcutta; includes a selection of his poems.